2007
DOI: 10.1590/s0100-72032007001000004
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre o estado nutricional pré-gestacional e a predição do risco de intercorrências gestacionais

Abstract: Artigos originais Resumo OBJETIVO: analisar a associação entre o estado nutricional pré-gestacional materno e os desfechos maternos-síndromes hipertensivas da gravidez, diabetes gestacional, deficiência de vitamina A e anemia-e do concepto-baixo peso ao nascer. MéTOdOs: estudo transversal, com 433 puérperas adultas (>20 anos), atendidas na Maternidade Escola da Universidade Federal do Rio de Janeiro (UFRJ) e seus respectivos recém-nascidos. As informações foram coletadas em consulta a prontuários e entrevistas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
36

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 0 publications
1
13
0
36
Order By: Relevance
“…Padilha et al 23 did not find an association between pre-pregnancy body mass index and anemia during pregnancy. However, in agreement with the present study, the aforementioned authors also observed that the frequency of anemia in women with gestational overweight or obesity increased gradually over time.…”
Section: Discussionmentioning
confidence: 90%
“…Padilha et al 23 did not find an association between pre-pregnancy body mass index and anemia during pregnancy. However, in agreement with the present study, the aforementioned authors also observed that the frequency of anemia in women with gestational overweight or obesity increased gradually over time.…”
Section: Discussionmentioning
confidence: 90%
“…The small number of pregnant women with a diagnosis of hypertension probably explains why this variable failed to reach statistical significance, although it was kept in the final model due to its clinical and epidemiological importance. Hypertensive complications in pregnancy (preeclampsia and eclampsia) are serious public health problems, among the leading causes of maternal and fetal morbidity and mortality 15 and also appear to be associated with pre-gestational nutritional status 29,30 . In this context, prenatal care is used as an indicator of the quality of care provided to the mother and infant, controlling risk factors potentially associated with pregnancy and implementing adequate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura demonstra que os extremos do estado nutricional antropométrico podem trazer riscos adicionais à gestação [18][19][20][21] . Conhecer os detalhes do consumo dietético aprimora a qualidade do atendimento e das orientações fornecidas.…”
Section: Discussionunclassified